The Impact of Cybercrime in Modern Generation Based on Systematic Literature Review Analysis - Kong, Ming Chai; Ang Zi Xuan; Abdullah, Muhaymin Hakim (Journal of Techno-Social, 2023)
Cybercrime is a term for any illegal activity that uses a computer as its primary means of commission. Due to the pervasive presence of the internet, the modern generation faces unprecedented challenges posed by cybercrime. Cybercrime has brought a lot of impacts to individuals, societies, and institutions in contemporary times. Sadly, it has become one of the most worrying issues in the current world. This study was done to determine the impact of cybercrime in modern generation. This research employs a qualitative approach by conducting a systematic literature review utilizing the PRISMA method. Moreover, it incorporates the outcomes of prior studies by employing a screening process to identify and critically access each one, thereby reestablishing their significance with the current study. The results of the study found impacts of cybercrime in modern generation which are financial consequences, expanding security budget, social implications, information security concern, and psychological and emotional toll.